T-regulatory cells subpopulation in bronchial asthma and heterogeneous phenotypes of chronic obstructive pulmonary disease - N. A. Kirillova; I. A. Deyev; Ye. E. Kremer; L. M. Ogorodova; G. E. Chernogoryuk (Бюллетень сибирской медицины)
Aim of the study was to investigate the levels of individual subpopulations of T-regulatory (T-reg) cells in patients with different phenotypes of chronic obstructive pulmonary disease (COPD) with moderate bronchial asthma and healthy volunteers. COPD was associated with increased level of natural (CD4+CD25high) T-cells, while emphysematous phenotype of disease was associated with the highest pool of natural CD4+CD25high. Bronchial asthma was associated with low levels of inducible (CD4+ FoxP3+ ) T-reg.